EFEK PENGGUNAAN PASIR BATU APUNG SEBAGAI PENGGANTI SEBAGIAN AGREGAT HALUS PADA CAMPURAN BETON RINGAN - Abdul Gaus; Mufti Amir Sultan; Raudha Hakim (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Lightweight concrete is obtained using pumice sand as a substitute for fine aggregate. The expected advantage of lightweight concrete is to reduce the self-weight of the concrete, which is a dead load on the structure. This study aims to determine the effect of using pumice sand on concrete volume weight, compressive and tensile strength. Research methods with testing in the laboratory. The test object used is cylindrical with a height of 30 cm and a diameter of 15 cm, according to SNI-03-1974. The coarse aggregate of pumice and the fine aggregate of pumice sand were sourced from the Dowora quarry on Tidore Island. Fine aggregate in control specimens using normal sand from the Kalumata quarry on Ternate Island. Using pumice sand as fine aggregate with a ratio of 75% normal sand, 20% pumice sand, 50% normal sand and 50% pumice sand, 25% normal sand and 75% pumice sand, and 100% pumice sand. Control test object using 100% normal sand. Each variation of the test object is ten pieces, so that the total test object is 50. The results of this study indicate that the volume weight decreased along with the addition of pumice sand weight into the concrete mixture. Therefore, If the volume of concrete produced is < 1900 kg/m3, the concrete is classified as lightweight. The resulting compressive strength of 56.63 kg/cm2 decreased to 81.10% of the control test object. The split tensile strength of concrete is 1.13 kg/cm2, or a decrease of 52.05% of the control test object. Based on the compressive and tensile strength, concrete is categorized as lightweight structural concrete as an insulator.